The Antecedents of Organizational Climate: The Emergence of Climate for Internal Service - Silenskyte, Ausrine (My University, 2012)
Purpose: This research seeks to explore how climate for internal service emerge in the organizations. Also, research aims to test how much the antecedents of climate for internal service are universal and similar among the countries. Design/methodology/approach: Using the case study for the in depth exploratory research, 16 semi-structured interviews based on the heuristic framework (constructed when utilizing Coleman’s bathtub model) were conducted in four bank departments in two countries (Lithuania and Latvia), interviewing managers and employees in each department; and HR manager of the bank in each country. Findings: Study provides broad variety of findings which shed light on climate emergence. Findings explain how interactions contribute to climate emergence (social capital and social exchange theory); suggest how and why size of the organization can contribute to climate emergence; presents what is the role of leaders and role of goal in climate emergence; what are the external factors that have an influence on climate for internal service emergence, etc. Moreover, study offers insights how climates interact with each other and demonstrates similarities in climate for internal service emergence across the countries. Research limitations/implications: More research is needed when investigating emergence of climate for internal service in a broader variety of culturally distant countries; in companies that has culturally diverse teams; and including individual (not only organizational) factors in the process of climate emergence. Practical implications: This study provides a list of issues that should be considered by the organization and its managers when creating a good internal collaboration among the organizational members and different departments or units. Originality/value: This research highly contributes to the uncharted field of climate emergence in the organizations.
Keywords: emergence of organizational climate; climate for internal service; interaction approach; climate antecedents; internal collaboration in organization.; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|